Konvergensi Jurnalistik Tabloid Metrolima Depok di Era Pandemi Covid-19 - Suwanto, Suwanto (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The MetroLima tabloid has converged by combining two media from print media with internet-based technology, thus creating a new identity, namely MetroLima.Com and MetroLima TV, as well as YouTube and Instagram channels. This step was taken to face business competition and the demands of the times which are all technology-based and of course will adapt to the digital industry. The purpose of this research is to find out how the convergence in the MetroLima Tabloid maintains print media in the current digital era by using technogenic practices in the media amid the Covid-19 pandemic, and how journalistic convergence is applied to the MetroLima tabloid. This study uses a qualitative approach method. Data collection techniques by observation and interviews as well as documentation, the selected informants are editor-in-chief and readers. The results of the study show the newsrom 3.0 convergence model where the news gathering process and content are carried out by one journalist and then to be distributed to all MetroLima Depok tabloid platforms, MetroLimaNews and MetroLima TV as well as MetroLima Depok tabloid social media. The newsroom model is to streamline human resources and summarize work mechanisms. MetroLima tabloid performs convergence using E Grant's theory which refers to 3 dimensions of convergence.